The Effect of Organizational Commitment and Organizational Culture on Employee Performance at DPRD Office Of Kabupaten Seluma - Puji Rahayu; Neri Susanti; Suswati Nasution (Journal of Indonesian Management, 2021)
The purpose of this study was to determine the effect of organizational commitment and organizational culture on employee performance. at the Seluma Regency DPRD Office. The sample in this study amounted to 35 employees at the Seluma Regency DPRD Office who have become government officers (ASN). The data was collected using a questionnaire, while the analytical methods used were multiple linear regression, determination test and hypothesis testing. The results of the regression analysis show Y = 1.501 + 0.380X1 + 0.603 X2 + e this describes a positive regression direction, meaning that there is a positive influence between X1 (organizational commitment) and X2 (organizational culture) on performance (Y). It means that if the variables of organizational commitment and organizational culture increase, it will increase performance. The value of the coefficient of determination is 0.590. This means that X1 (organizational commitment) and X2 (organizational culture) affect performance (Y) by 59% while the remaining 41% is influenced by other variables not examined in this study. The results of the t test at a significance level of 0.05 explain that partially organizational commitment variables and organizational culture have a significant influence on employee performance variables at the Seluma Regency DPRD Office. The results of the F test at a significance level of 0.05 explain that organizational commitment variables and organizational culture have a significant simultaneous influence on employee performance at the DPRD office of Seluma Regency because the significant value of 0.000 is smaller than 0.05.